CAROLLINE: A Caged Rolling Drone With Omnidirectional Ground Mobility and Simple Implementation - Sim, Seunghyeon; Kim, Donghyeong; Lee, Changhyeon; Jung, Jooyeol; Park, Jinwoo; Yoon, Seongwon; Han, Soohee (Institute of Electrical and Electronics Engineers Inc., 2025)
In this letter, we propose modeling and control design of a caged rolling drone, called CAROLLINE, that is capable of both ground and aerial locomotion with simple implementation. Specifically, omnidirectional ground mobility is achieved without additional actuators or devices, which contributes to miniaturization and operational efficiency of CAROLLINE. A mathematical model of CAROLLINE is constructed to design an appropriate controller for holonomic locomotion and to assume a pre-takeoff posture from any initial attitude. The overall control scheme is modularly composed and integrated well with the existing drone system. The proposed rolling on the ground provides 12.6 times higher energy efficiency than conventional flight. Experimental validation was also conducted to demonstrate the actual performance of CAROLLINE.